Answer:
huh
Step-by-step explanation:
Answer:
<h3>n = 1/4</h3>
Step-by-step explanation:
![2^2 \times 2n= (2)\\\\\mathrm{Simplify\:}2^2\times\:2n:\quad 8n\\\\\mathrm{Simplify\:}\left(2\right):\quad 2\\\\8n=2\\\\\mathrm{Divide\:both\:sides\:by\:}8\\\\\frac{8n}{8}=\frac{2}{8}\\\\Simplify\\\\n=\frac{1}{4}](https://tex.z-dn.net/?f=2%5E2%20%5Ctimes%202n%3D%20%282%29%5C%5C%5C%5C%5Cmathrm%7BSimplify%5C%3A%7D2%5E2%5Ctimes%5C%3A2n%3A%5Cquad%208n%5C%5C%5C%5C%5Cmathrm%7BSimplify%5C%3A%7D%5Cleft%282%5Cright%29%3A%5Cquad%202%5C%5C%5C%5C8n%3D2%5C%5C%5C%5C%5Cmathrm%7BDivide%5C%3Aboth%5C%3Asides%5C%3Aby%5C%3A%7D8%5C%5C%5C%5C%5Cfrac%7B8n%7D%7B8%7D%3D%5Cfrac%7B2%7D%7B8%7D%5C%5C%5C%5CSimplify%5C%5C%5C%5Cn%3D%5Cfrac%7B1%7D%7B4%7D)
Answer:
d=4.14
Step-by-step explanation:
use the equation d=2r
d=C/π=13/π≈4.13803
4.13803≈4.14
Answer:
The student incorrectly simplified 10ab root 2a + 20a root 2a
Step-by-step explanation:
Answer:
Therefore
, A=184
Step-by-step explanation:
Given function is
![T(t)=230 -e^{-kt}](https://tex.z-dn.net/?f=T%28t%29%3D230%20-e%5E%7B-kt%7D)
where T(t) is the temperature in °C and t is time in minute and A and k are constants.
She noticed that after 18 minutes the temperature of the pie is 138°C
Putting T(t) =138°C and t= 18 minutes
![138=230 -Ae^{-k\times 18}](https://tex.z-dn.net/?f=138%3D230%20-Ae%5E%7B-k%5Ctimes%2018%7D)
![\Rightarrow -Ae^{-18k}=138-230](https://tex.z-dn.net/?f=%5CRightarrow%20%20-Ae%5E%7B-18k%7D%3D138-230)
.....(1)
Again after 36 minutes it is 184°C
Putting T(t) =184°C and t= 36 minutes
![184=230-Ae^{-k\times 36}](https://tex.z-dn.net/?f=184%3D230-Ae%5E%7B-k%5Ctimes%2036%7D)
![\Rightarrow Ae^{-36k}=230-184](https://tex.z-dn.net/?f=%5CRightarrow%20Ae%5E%7B-36k%7D%3D230-184)
.......(2)
Dividing (2) by (1)
![\frac{Ae^{-36k}}{Ae^{-18k}}=\frac{46}{92}](https://tex.z-dn.net/?f=%5Cfrac%7BAe%5E%7B-36k%7D%7D%7BAe%5E%7B-18k%7D%7D%3D%5Cfrac%7B46%7D%7B92%7D)
![\Rightarrow e^{-18k}=\frac{46}{92}](https://tex.z-dn.net/?f=%5CRightarrow%20e%5E%7B-18k%7D%3D%5Cfrac%7B46%7D%7B92%7D)
Taking ln both sides
![ln e^{-18k}=ln\frac{46}{92}](https://tex.z-dn.net/?f=ln%20e%5E%7B-18k%7D%3Dln%5Cfrac%7B46%7D%7B92%7D)
![\Rightarrow -18k =ln (\frac12)](https://tex.z-dn.net/?f=%5CRightarrow%20-18k%20%3Dln%20%28%5Cfrac12%29)
![\Rightarrow -18k= ln1-ln2](https://tex.z-dn.net/?f=%5CRightarrow%20-18k%3D%20ln1-ln2)
![\Rightarrow k= \frac{ln2 }{18}](https://tex.z-dn.net/?f=%5CRightarrow%20k%3D%20%5Cfrac%7Bln2%20%7D%7B18%7D)
Putting the value k in equation (1)
![Ae^{-18\frac{ln2}{18}}=92](https://tex.z-dn.net/?f=Ae%5E%7B-18%5Cfrac%7Bln2%7D%7B18%7D%7D%3D92)
![\Rightarrow A e^{ln2^{-1}}=92](https://tex.z-dn.net/?f=%5CRightarrow%20A%20e%5E%7Bln2%5E%7B-1%7D%7D%3D92)
![\Rightarrow A.2^{-1}=92](https://tex.z-dn.net/?f=%5CRightarrow%20A.2%5E%7B-1%7D%3D92)
![\Rightarrow \frac{A}{2}=92](https://tex.z-dn.net/?f=%5CRightarrow%20%5Cfrac%7BA%7D%7B2%7D%3D92)
![\Rightarrow A= 92 \times 2](https://tex.z-dn.net/?f=%5CRightarrow%20A%3D%2092%20%5Ctimes%202)
⇒A= 184.
Therefore
, A=184